Nasal width as a guide for the selection of maxillary complete denture anterior teeth in four racial groups - Varjão, Fabiana Mansur [UNESP]; Nogueira, Sergio Sualdini [UNESP] (Wiley, 2006)
Purpose: Selecting artificial teeth for edentulous patients is difficult when pre-extraction records are not available. Various guidelines have been suggested for determining the width of the maxillary anterior denture teeth. This study was undertaken to evaluate the use of the nasal width as a guide for the selection of proper width maxillary anterior denture teeth in four racial groups of the Brazilian population. Materials and Methods: One hundred and sixty subjects (40 Whites, 40 Mulattos, 40 Blacks, and 40 Asians) were selected. Using a sliding caliper, the nasal width and the intercanine distance were measured. The Pearson product-moment correlation coefficient was used to determine the relationship between the above measurements. A prediction was made of the percentage of subjects of the White, Mulatto, Black, and Asian populations in which the selection error due to the clinical application of the method of the nasal width would be within 0 to 2 mm, within 2 to 4 mm, and greater than 4 mm. Results: The four racial groups showed a weak correlation between the intercanine distance and the nasal width. In 39.7% of the White, 55.7% of the Mulatto, 81.9% of the Black, and 48.2% of the Asian populations, errors greater than 4 mm would be present with the use of the nasal width. Conclusions: The correlation found between the intercanine distance and the nasal width was not high enough to be used as a predictive factor. The relationship between natural tooth width and artificial tooth width as predicted by the nasal width showed that the nasal width method is not accurate for all the studied groups. Copyright © 2006 by The American College of Prosthodontists.
Keywords: Artificial teeth; Complete denture; Dental esthetics; Race; adolescent; adult; Asian; Brazil; Caucasian; denture; ethnology; female; histology; human; male; methodology; Negro; nose; odontometry; reference value; tooth prosthesis; Adolescent; Adult; African Continental Ancestry Group; Asian Continental Ancestry Group; Denture Design; European Continental Ancestry Group; Female; Humans; Male; Nose; Odontometry; Reference Values; Tooth, Artificial